The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3892/mmr.2021.12459
|View full text |Cite
|
Sign up to set email alerts
|

HOXD9‑induced SCNN1A upregulation promotes pancreatic cancer cell proliferation, migration and predicts prognosis by regulating epithelial‑mesenchymal transformation

Abstract: Pancreatic cancer (PC) is a malignant tumor disease, whose molecular mechanism is not fully understood. Sodium channel epithelial 1α subunit (SCNN1A) serves an important role in tumor progression. The current study explored the role of homeobox D9 (HOXD9) and SCNN1A in the progression of PC. The expression of SCNN1A and HOXD9 in PC samples was predicted on online databases and detected in PC cell lines. The association between SCNN1A expression and PC prognosis was examined by the Gene Expression Profiling Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…However, CLIC6 has no reported significance in tumorigenesis and tumor progression to date. SCNN1A promotes ovarian and pancreatic cancer cell proliferation and migration and inhibits osteosarcoma growth [48,49]. Nevertheless, the specific biological functions of CLIC6 and SCNN1A in PCa warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, CLIC6 has no reported significance in tumorigenesis and tumor progression to date. SCNN1A promotes ovarian and pancreatic cancer cell proliferation and migration and inhibits osteosarcoma growth [48,49]. Nevertheless, the specific biological functions of CLIC6 and SCNN1A in PCa warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…SCNN1A downregulation inhibited cell proliferation, migration and invasion, and induced cell apoptosis. Another study showed that SCNN1A upregulation by homeobox D9 (HOXD9) induced cell proliferation and migration in pancreatic cancer cells [ 52 ]. Cai et al demonstrated that inhibition of Serine Protease 8 (PRSS8)/SCNN1A by sterol regulatory element binding protein 2 (SREBF2) reduced the cell proliferation, migration, and epithelial–mesenchymal transformation of ovarian cancer [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis of the gene expression in the tissues from the patients with lung adenocarcinoma revealed possible implications of ASIC1, ASIC2, ASIC3, ASIC4, α-ENaC, and γ-ENaC in the disease progression ( Figure 9A ). Indeed, all these channels are involved in acidosis-induced tumor progression: ASIC1 and α-ENaC mediate the epithelial–mesenchymal transition of pancreatic cancer ( 19 , 40 ), while ASIC2 promotes the invasion and metastasis of colorectal cancer ( 41 ). Interestingly, ASIC3, which is down-regulated in lung adenocarcinoma samples, may also drive the migration of pancreatic cancer cells ( 19 ), so its role in cancer progression may depend on the carcinoma type.…”
Section: Discussionmentioning
confidence: 99%